2011
DOI: 10.1097/aog.0b013e31821fd360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity on Oocyte and Embryo Quality in Women Undergoing In Vitro Fertilization

Abstract: Obesity was associated with fewer normally fertilized oocytes, lower estradiol levels, and lower pregnancy and live birth rates. Infertile women requiring IVF should be encouraged to maintain a normal weight during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
140
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(153 citation statements)
references
References 34 publications
6
140
0
2
Order By: Relevance
“…The largest study in the literature on oocyte and embryo parameters reported fewer than two pronuclei embryos, lower clinical pregnancy, and live birth rates in their obese patients [16] compared with normal-weight controls. In this study, there was no association between obesity and the quality of day 3 embryos.…”
Section: Introductionmentioning
confidence: 99%
“…The largest study in the literature on oocyte and embryo parameters reported fewer than two pronuclei embryos, lower clinical pregnancy, and live birth rates in their obese patients [16] compared with normal-weight controls. In this study, there was no association between obesity and the quality of day 3 embryos.…”
Section: Introductionmentioning
confidence: 99%
“…However, lean women achieved higher CPR and live birth rate compared to the overweight and obese women. It is assumed that obesity alters the follicular androgen profile, insulin resistance and is associated with elevated leptin levels which inversely affect oocyte size, oocyte and embryo quality; changes that may be responsible for the poor outcome in overweight and obese PCOS women 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In non-PCOS women, BMI has been shown to affect IVF outcome 10,11 . However, in women with PCOs, the effect of BMI on IVF/ICSI outcome has not been fully evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Patient concern that being overweight or obese is detrimental to IVF success may contribute to the finding that over 60 % of survey respondents considered it helpful for men and women to exercise rigorously during the IVF cycle [2,3,14]. While the impact of rigorous exercise during the IVF cycle has not been completely characterized, existing literature suggests vigorous exercise, whether current or former, is associated with worse outcomes [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest certain lifestyle behaviors and patient characteristics such as being underweight or obese adversely affect cycle success [2,3], while stress-reducing behaviors are generally thought to be beneficial [4,5]. Meanwhile, some popularly supported behaviors, such as complete bed rest after embryo transfer, have not been shown to improve outcomes [6,7].…”
Section: Introductionmentioning
confidence: 99%